Gods and scholars: archaeologies of religion in the Near East. (15th September 2016) - Rowan, Yorke
Abstract : These two edited volumes reflect the continuing surge of interest in the archaeology of religious practice and belief. Over the past 20 years, archaeologists have turned their focus on the study of ritual and religion, challenging what Hawkes (1954 : 162) considered the highest and most difficult to reach rung on his ladder of inference: "religious institutions and spiritual life". Renewed interest in the archaeology of religion and ritual was largely inspired by Renfrew's (1985 ) work on the Bronze Age Phylakopi sanctuary on Melos, Greece, a seminal study that continues to guide archaeological interpretation based on the material correlates linked with ritual practice. Renfrew's focus on ritual (or 'cult') exposed the widespread perception that religion is archaeologically inaccessible. The recognition that a Durkheimian division between the sacred and the profane is less distinct in reality, particularly in small-scale rituals and domestic contexts, complicates the difficulty archaeologists face in the hazy area between quotidian life and religious praxis. Since Renfrew's publication of Phylakopi, these problems have been recognised and confronted in a variety of different volumes and synthetic articles.